Pendampingan Peningkatan Usaha Seblak Guna Meningkatkan Penjualan - Emerentia, Kharens; Wadu, Christian Vallentino; Setiawan, Ivonne Averina; Narwasti, Eimel; Sarvia, Elty; Wianto, Elizabeth; Christina, Christina; Leony, Florence; Arisandhy, Vivi (Universitas Nusantara PGRI Kediri, 2023)
UMKM (micro, small and medium enterprises) in Indonesia are growing in a better direction. The government also supports the development of UMKM to recover Indonesia’s economy since the Covid-19 Pandemic. Community Service activities are carried out to provide direction and suggestions for problems experienced by Seblak Basreng business actors. The method used is descriptive research with a qualitative approach. Data collection was carried out by conducting semi-structured interviews, observation, and social media analysis used by Seblak Basreng Teh Dini. The findings from the activities that have been carried out are that the people of Bandung do not know about Seblak Basreng Teh Early, locations that are difficult for new customers to find, product photos on pages on Grab Food and Gofood are less attractive, and do not yet have a cashless payment method. The proposal that has been implemented is to expand customers for Seblak Basreng Teh Early, it is necessary to carry out promotions to promote their wares using Instagram, Facebook, and Tiktok; make banners and road signs; improvement of product photos on Grab Food and Gofood pages; and making QRis. The recommendation that can be conveyed is the continuation of the mentoring program for other business actors so that they can implement and manage digital media optimally.